Farmland values and agricultural growth: The case of Chile - Guillermo Donoso; José Cancino; William Foster (Economía Agraria y Recursos Naturales)
This study analyzes the relationships between farmland values and factors associated with the growth in Chilean agriculture, and identifies agricultural land value’s determinants by estimating a log-linear hedonic price function. The results indicate that a parcel’s market value varies according to its suitability and productivity for different crops, its location and transport costs, its potential for residential use, and other factors that determine expectations of future income streams. Farms with soil aptitude for fruits, high-valued export-oriented crops that have led Chile’s agricultural boom, have higher values than those with forestry soil aptitude.